PEER EDUCATION DAN KESADARAN TERKAIT HIV/AIDS DI LAPAS - Komalasari, Rita (JURNAL KESEHATAN KARTIKA, 2023)
Background: This paper presents research results that can provide insight into the importance of Peer education in an effort to raise awareness related to HIV/AIDS in Lapas. Regarding the research method, the case study at Sukabumi Prison, Indonesia will be used to gain a deep understanding of Peer education benefits related to HIV/AIDS. Institutional perspectives will be explored by conducting interviews to security, administrative, and support staff members such as health care workers. Result: female respondents who had attended the peer education program did not mind daily making contact with HIV-positive inmates, Conclusion: the findings presented in this paper contributed to the strengthening of the Peer education policies and programs related to HIV/AIDS in Lapas.